Marine Sponge Dysidea herbacea revisited: Another Brominated Diphenyl Ether - Bruce F. Bowden; Madhavi S. Agrawal (Marine Drugs, 2005)
Abstract: A pentabrominated phenolic diphenyl ether (1) that has not previously been reported from marine sources has been isolated from Dysidea herbacea collected at Pelorus Island, Great Barrier Reef, Australia. The structure was determined by comparison of NMR data with those of known structurally-related metabolites. NMR spectral assignments for (1) are discussed in context with those of three previously reported isomeric pentabrominated phenolic diphenyl ethers.